2023
DOI: 10.1002/uog.26178
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypotonia: systematic approach for prenatal detection

Abstract: What are the novel findings of this work?This is the first study to address the prenatal manifestation and diagnosis of congenital hypotonia as a single condition. The overall prenatal detection rate of congenital hypotonic conditions in our cohort was 38.5%. Only cases which underwent a targeted scan were detected and, among the cases which underwent this scan, the prenatal detection rate was 62.5%. A proposed diagnostic strategy that involved performing a targeted scan for a single non-specific ultrasound si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…This might have led to a higher detection of anomalies. This type of bias has been previously reported40 41 and should be kept in mind in comparative studies. As the current study does not compare the study group with a control group, this bias is of less concern.…”
Section: Discussionmentioning
confidence: 75%
“…This might have led to a higher detection of anomalies. This type of bias has been previously reported40 41 and should be kept in mind in comparative studies. As the current study does not compare the study group with a control group, this bias is of less concern.…”
Section: Discussionmentioning
confidence: 75%
“…We report three cases of neonates with congenital hypotonia identified postnatally, whose only prenatal manifestation was polyhydramnios. In a recent retrospective study, the reported prenatal detection rate of congenital hypotonia was 38.5% [ 3 ]. In the aforementioned study, polyhydramnios was detected in significantly more singleton pregnancies in the group of hypotonic neonates compared to the group of unaffected newborns (64% vs 3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In the aforementioned study, polyhydramnios was detected in significantly more singleton pregnancies in the group of hypotonic neonates compared to the group of unaffected newborns (64% vs 3%, respectively). The authors proposed that targeted scanning combined with genetic testing in pregnancies demonstrating non-specific sonographic signs, such as hydramnios, persistent breech presentation, fetal growth restriction, and maternal reporting of reduced fetal movement would increase the detection rate of congenital hypotonia up to 88.5% [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She had an uneventful term scheduled delivery via cesarean section, with an Apgar score of 9/9, birth weight of 3740 g (60th percentile) and macrocephaly with HC of 360 mm (above the 90th percentile). The neonate remained in the hospital for 6 weeks due to complications expected with Sotos syndrome, such as the need for respiratory assistance, hypotonia, neonatal hypoglycemia and feeding difficulties 1,2 . Sotos syndrome was clinically confirmed, and the child was enrolled in pediatric neurological surveillance, and by 6 months of age had already displayed motor neurodevelopmental delays, lagging in achieving developmental milestones, and large HC.…”
Section: Casementioning
confidence: 99%